Understanding Customers’ Continuance Intentions Toward In-Lobby Self-Service Technologies - Li, Mingfei; Huang, Shanshan (Frontiers in Psychology, 2019)
Drawing on service climate theory and insights from the literature on self-service technologies and customer participation, this study investigates the antecedents of customers’ continuance intentions toward in-lobby self-service technologies (SSTs). Using data collected from 257 actual customers in the context of retail banks, this experimental study examines the proposed relationship between customer perceived service climate, customer readiness factors (i.e., perceived ability, role clarity, and perceived benefit), customer satisfaction and customer continuance intention toward in-lobby self-service technologies. The results show that customers’ perceived service climate positively influences customers’ continuance intentions toward in-lobby SSTs. Moreover, two customer readiness factors (i.e., perceived ability, perceived benefit) and customer satisfaction mediate this relationship. The findings demonstrate the importance of customers’ perceived service climate in driving their continuance intention and provide managerial implications for service firms employing in-lobby self-service technologies.